Dominant‐negative effects of KCNQ2 mutations are associated with epileptic encephalopathy. Issue 3 (18th March 2014) - Orhan, Gökce; Bock, Merle; Schepers, Dorien; Ilina, Elena I.; Reichel, Stephanie Nadine; Löffler, Heidi; Jezutkovic, Nicole; Weckhuysen, Sarah; Mandelstam, Simone; Suls, Arvid; Danker, Timm; Guenther, Elke; et al.
<x xml:space="preserve">Abstract</x> Objective Mutations in KCNQ2 and KCNQ3, encoding the voltage‐gated potassium channels KV7.2 and KV7.3, are known to cause benign familial neonatal seizures mainly by haploinsufficiency. Here, we set out to determine the disease mechanism of 7 de novo missense KCNQ2 mutations that were recently described in patients with a severe epileptic encephalopathy including pharmacoresistant seizures and pronounced intellectual disability. Methods Mutations were inserted into the KCNQ2 cDNA. Potassium currents were recorded using 2‐microelectrode voltage clamping, and surface expression was analyzed by a biotinylation assay in cRNA‐injected Xenopus laevis oocytes. Results We observed a clear loss of function for all mutations. Strikingly, 5 of 7 mutations exhibited a drastic dominant‐negative effect on wild‐type KV7.2 or KV7.3 subunits, either by globally reducing current amplitudes (3 pore mutations) or by a depolarizing shift of the activation curve (2 voltage sensor mutations) decreasing potassium currents at the subthreshold level at which these channels are known to critically influence neuronal firing. One mutation significantly reduced surface expression. Application of retigabine, a recently marketed KV7 channel opener, partially reversed these effects for the majority of analyzed mutations. Interpretation The development of severe epilepsy and cognitive decline in children carrying 5 of the 7 studied KCNQ2 mutations can be related to a dominant‐negative reduction of the resulting potassium current at subthreshold membrane potentials. Other factors such as genetic modifiers have to be postulated for the remaining 2 mutations. Retigabine or similar drugs may be used as a personalized therapy for this severe disease. Ann Neurol 2014;75:382–394